SUPPOSED PROCESS IMPLEMENTATION OF THE QUALITY MANAGEMENT SYSTEM BY ISO 9001 AT JAN PERNER TRANSPORT FACULTY UNIVERSITY OF PARDUBICE - Svadlenka, Libor; Cempirkova, Eva (Doprava a spoje, 2007)
Implementing of QMS in education (in particular university) is connected with complications, whose resorts can be:. connective problematic of QMS only with processes of technical control and test products and within connecting misunderstanding correct functions of QM, . representative selection of school direction on the principle of standard criterions research and pedagogic activity and no after manager competences, whose are these functions especially the manager functions,. minimum range of education training of executive staff in manger techniques and entrances,. ignorance of your customer on the part of majority school workmen, soft competitive environment,. short possibility of school regulation with respect to management standard,. soft competitive environment.